HUBUNGAN ANTARA STRES AKADEMIK DAN MOTIVASI BELAJAR SISWA LATAR BELAKANG EKONOMI KURANG MAMPU - Oktavina May Anja; Doddy Hendro Wibowo (Bajang Institute, 2023)
Problems experienced by students in education can make their learning motivation lower and result in lower grades. This study aims to determine the relationship between academic stress and learning motivation of students with poor economic backgrounds. The sampling technique used simple random sampling with a sample size of 100 subjects. Data collection of academic stress was measured using the perception of academic stress scale and learning motivation was measured using the Learning motivation scale. The data analysis technique used is Pearson Correlation. The results showed that there was a significant negative relationship between academic stress and learning motivation of students with poor economic background (r = 0.356 and sig. = 0.000). This indicates that academic stress is not the main factor that hinders the increase in learning motivation of students from economically disadvantaged backgrounds.